2019
DOI: 10.1111/vsu.13218
|View full text |Cite
|
Sign up to set email alerts
|

Survey of instructor and student impressions of a high‐fidelity model in canine ovariohysterectomy surgical training

Abstract: Objective: To evaluate the usefulness of a high-fidelity model for teaching ovariohysterectomy (OHE) to veterinary students. Study design: Longitudinal survey. Sample population: Clinicians with ≥2 years postgraduate experience in small animal surgery and a sophomore veterinary student population at 1 institution. Methods: Twelve clinicians evaluated the high-fidelity model for realism. Questionnaires were distributed to sophomore veterinary students prior to and after OHE training on the high-fidelity model (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Studies collecting validity evidence and educational outcome studies are more valuable to educators than descriptive studies, or studies collecting only student or faculty opinion data that provide weaker data. Of the 14 studies published in 2019 and 2020, two studies collected validity evidence for models and rubrics, 15,16 three evaluated high-fidelity models, [17][18][19] two ran direct comparisons of two models to evaluate learning outcomes, 20,21 and five collected performance data on the live animal or a cadaver. 15,16,18,20,22…”
Section: Rate Of Growthmentioning
confidence: 99%
“…Studies collecting validity evidence and educational outcome studies are more valuable to educators than descriptive studies, or studies collecting only student or faculty opinion data that provide weaker data. Of the 14 studies published in 2019 and 2020, two studies collected validity evidence for models and rubrics, 15,16 three evaluated high-fidelity models, [17][18][19] two ran direct comparisons of two models to evaluate learning outcomes, 20,21 and five collected performance data on the live animal or a cadaver. 15,16,18,20,22…”
Section: Rate Of Growthmentioning
confidence: 99%
“…Rezende-Filho et al (2014) reported on a student-centred approach to active learning through the construction of teaching tools in medical physiology. Other studies have found high-fidelity models and simulators realistic, engaging and efficient, and that such training has good transferability to clinical settings (Kinnison et al, 2009;Salas et al, 2009;Grant et al, 2010;Griswold et al, 2012;Marker et al, 2019;Yong et al, 2019;Jaskowski et al, 2020). The systematic review by McLaughlin et al (2019) revealed that "simulation-based training for trauma resuscitation is associated with improved measures of teamwork, task performance and speed, knowledge and provider satisfaction".…”
Section: Are Existing Models Adequate?mentioning
confidence: 99%
“…For example, research and development in education and training in laboratory animal science is behind in the range of scenarios and fidelity of simulators available, as well as in the evaluation of learning outcomes, showing that more investment is needed to promote the use of alternatives in this area. However, for any acquisition of skills that will be necessary in future clinical or laboratory practice, simulation-based training without harmful use of animals or humans has proved to be an adaptable methodology to meet any training needs and a suitable practice to improve the knowledge and skills of trainees and the outcomes of patients (Salas et al, 2009;Grant et al, 2010;Griswold et al, 2012;Rubeis and Steger, 2018;Marker et al, 2019;Yong et al, 2019).…”
Section: Are Existing Models Adequate?mentioning
confidence: 99%
“…3 While the use of a "flipped classroom" and self-directed learning techniques have become commonplace in some disciplines, veterinary surgical training has remained a discipline that is primarily taught in person with models, high fidelity simulators, and animals. [4][5][6] With the onset of the global pandemic and restrictions regarding participant gathering and close contact, a requirement for socially distanced surgical veterinary education developed. Because of the status of the pandemic at the time of writing, it is reasonable to expect that social distancing requirements may continue to persist for the foreseeable future, thus requiring continued implementation of remote teaching strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The ethical responsibility to reduce the number of animals used 1,2 and the financial burden of providing animals for increased veterinary class size has led to development of quality online resources, high fidelity models and simulators, and case‐based scenarios to complement veterinary surgical training 3 . While the use of a “flipped classroom” and self‐directed learning techniques have become commonplace in some disciplines, veterinary surgical training has remained a discipline that is primarily taught in person with models, high fidelity simulators, and animals 4‐6 …”
Section: Introductionmentioning
confidence: 99%